Telerobotic Systems in Medicine: Challenges and Potential - Avgousti, Sotiris; Masouras, Panicos; Christoforou, Eftychios G.; Panayides, Andreas S.; Vieyres, Pierre; Novales, Cyril (My University, 2018)
Telerobotics is part of the wider field of telemedicine. The ultimate goal of telemedicine is to provide specialized healthcare services over long distances. The possibility of consultation diagnosis, treatment, and medical intervention from a distance, may greatly impact the quality of life of patients located in isolated areas where access to specialized medical services is limited. Practically, a specialist can examine or operate on a patient at a different geographic location without either of them having to travel. Costs and inconvenience are avoided while improved access to information becomes possible. Moreover, the physician can provide services while at a more comfortable working environment. Apart from medically-isolated areas, telemedicine is also expected to play a role in removing barriers to healthcare provision in developing countries, in areas of natural disasters, and war zones where consistent healthcare is unavailable or there is no time to transport a patient to a hospital. The primary objective of this study was to present a systematic review of telerobotic systems and highlight their challenges but also their potential.